More “Kingdom”, less “religiosity”: a new paradigm for evangelical youth in public space? - Aguiar, Taylor de (FCL-UNESP Laboratório Editorial, 2021)
This text discusses the presence, among evangelical youth in Porto Alegre/RS,Brazil, of an ecclesiological ideology known as “Kingdom culture”, which is opposed to what young participants from different denominations consider a negative model of “religiosity”. It emphasizes how the notion of “Kingdom” is the starting point for a paradigm shift in youth evangelical relations with “culture” and the secular. It is demonstrated that the “Kingdom” imposes new theoretical challenges to the investigations on the evangelical presence in the public space, demanding an analysis which takes into account the multiple aspects of what is natively understood by “Kingdom”, and which seeks simultaneously, to understand the activation of the “religiosity” category from a descriptive undertaking of the articulations of concepts. Moreover, reflections on the generational character of the “Kingdom culture” movement are still within the scope of this article, seeking to understand it as a manifestation associated with young evangelicals who live the present “spirit of the time”.